Incidental Stigmatisation? - Freya Sukalla; Veronika Karnowski (University of Zurich, IKMZ - Department of Communication and Media Research, 2022)
More and more individuals turn to apps to increase their well-being or reduce stress, with meditation apps being most popular to achieve these goals. However, considering the underlying normative imperative of idealised self-help inherent in the well-being app market, concerns have been raised that these apps and how they are promoted on the app market might contribute to the stigma of mental illness. To explore these potential detrimental effects we conducted a pre-registered experimental survey study (N = 249) examining whether (1) the emphasis on individual responsibility for one's well-being in the text describing the app in the app market and (2) the lack of a disclaimer that the app is not a replacement for medical treatment increase both the stigmatisation of individuals with depression and self-stigmatisation. While our findings did not support our a priori hypotheses, further exploratory analyses uncovered more complex relationships between our experimental factors, respondents' age and prior experiences with mental illness, and stigmatisation and self-stigmatisation. We, therefore, call for future empirical investigations to better assess the risk of incidental stigmatisation through how well-being apps are promoted in the app market.